The women at Al-Sakhaawi Book "A;-Dhau Al-Lami", Study in the social life - بلقيس عيدان لويس (College of Education for Women, 2019)
In our previous research , we study the method of women by ( al - sakhaawi " died 902 ah/1496a.c"book witch called ( al- dhau, al-lami) . So in this paper , we will discuss the social life of women in the mamluk period through the same book ,especially when the sakhaawi devoted a full part for women in the same book called it (mhagam ,al -nessa)wich it translations a large number of women like wives ,daughters ,sisters ,and maids of mamluk sultans ,so that make my able to know a lot about the social life of woman which we study it like a social aspects of women, here wealth, business, professions ,and in the last we study the habits of them marriage .